Influence of HIV co-infection on clinical presentation and disease outcome in hospitalized adults with tuberculous meningitis in Brazil: a nationwide observational study - Urmenyi, Lucas G.; Vinhaes, Caian L.; Villalva-Serra, Klauss; Araujo-Pereira, Mariana; Andrade, Bruno B. (Frontiers in Public Health, 2025)
IntroductionTuberculous meningitis (TBM) is a severe form of central nervous system infection caused by Mycobacterium tuberculosis (Mtb) that is often associated with significant morbidity and mortality, particularly in people living with HIV (PLWH). This study investigated differences in clinical and laboratory profiles of TBM cases in Brazil associated with HIV status, and identified factors associated with in-hospital mortality.MethodsWe conducted a retrospective analysis of 1,819 hospitalized adult TBM patients reported in the Brazilian Notifiable Diseases Information System (SINAN) meningitis database from 2007 to 2021. Confirmed cases in hospitalized individuals aged >18 years with known HIV status were included; pregnant patients were excluded. Clinical and laboratory features were compared by HIV status and clinical outcomes. Classification and regression tree analysis was used to identify outcome-based cut-off values for selected continuous variables. Associations with in-hospital mortality were assessed using backward stepwise binomial logistic regressions.ResultsThe majority (57%) of TBM cases comprised of PLWH, who exhibited lower frequencies of vomiting, nuchal rigidity, signs of meningeal inflammation, and coma, along with lower leukocyte counts in cerebrospinal fluid (CSF) compared to HIV-negative patients. PLWH also displayed lower mortality rates (17.3% vs. 23.2%, p = 0.002). Features independently associated with mortality included seizures (aOR: 2.15, 95%CI: 1.39–3.33, p < 0.001), nuchal rigidity (aOR: 1.57, 95%CI: 1.1–2.23, p = 0.014), age > 64 years old (aOR: 2.11, 95%CI: 1.08–4.13, p = 0.03), CSF protein concentration ≥441 mg/dL (aOR: 2:08, 95%CI: 1.39–3.09, p < 0.001) and CSF glucose concentration ≥ 22 mg/dL (aOR: 0.54, 95%CI: 0.38–0.76, p < 0.001), but not HIV (OR: 0.73, [95%IC: 0.52–1.01], p = 0.06).ConclusionOur findings suggest that despite greater prevalence in PLWH, these patients present fewer clinical signs and symptoms and lower mortality rates. Additionally, HIV was not an independent predictor of mortality in this study population.